COMPARATIVE STUDY ON MAIN SOLVENCY ASSESSMENT MODELS FOR INSURANCE FIELD - Daniela Nicoleta SAHLIAN (Challenges of the Knowledge Society)
During the recent financial crisis of insurance domain, there were imposed new aspects that have to be taken into account concerning the risks management and surveillance activity. The insurance societies could develop internal models in order to determine the minimum capital requirement imposed by the new regulations that are to be adopted on 1 January 2016. In this respect, the purpose of this research paper is to offer a real presentation and comparing with the main solvency regulation systems used worldwide, the accent being on their common characteristics and current tendencies. Thereby, we would like to offer a better understanding of the similarities and differences between the existent solvency regimes in order to develop the best regime of solvency for Romania within the Solvency II project. The study will show that there are clear differences between the existent Solvency I regime and the new approaches based on risk and will also point out the fact that even the key principles supporting the new solvency regimes are convergent, there are a lot of approaches for the application of these principles. In this context, the question we would try to find the answer is "how could the global solvency models be useful for the financial surveillance authority of Romania for the implementation of general model and for the development of internal solvency models according to the requirements of Solvency II" and "which would be the requirements for the implementation of this type of approach?". This thing makes the analysis of solvency models an interesting exercise.